Differential expression of CD8 defines phenotypically distinct cytotoxic T cells in cancer and multiple sclerosis. Issue 12 (11th December 2022) - Burkard, Tobias; Herrero San Juan, Martina; Dreis, Caroline; Kiprina, Anastasiia; Namgaladze, Dmitry; Siebenbrodt, Kai; Luger, Sebastian; Foerch, Christian; Pfeilschifter, Josef M.; Weigert, Andreas; Radeke, Heinfried H.
Abstract: Background: Cytotoxic T lymphocytes take on a leading role in many immune‐related diseases. They function as key effector immune cells fighting cancer cells, but they are also considerably involved in autoimmune diseases. Common to both situations, CD8 + T cells need to adapt their metabolism and effector function to the harsh and nutrient‐deprived conditions of the disease‐associated microenvironment. Methods: We used an in vitro starvation as well as rapamycin treatment protocol mimicking nutrient deprivation to generate CD8 Low versus CD8 High T cells and performed FACS‐Sorting followed by transcriptomic profiling of the cytotoxic T cell subsets. Prominent markers identified in the CD8 Low versus the CD8 High T cells were then used to investigate the presence of these cell subsets in immune‐related human diseases. Employing cancer tissue microarrays and PhenOptics multispectral imaging as well as flow cytometry, we studied these CD8 + T cell subsets in cancer and relapsing‐remitting multiple sclerosis patients. Results: Starvation induced a decreased expression of CD8, yielding a CD8 Low T cell subpopulation with an altered transcriptomic signature and reduced effector function. CD8 Low T cell showed enhanced ST2L and IL6ST (CD130) expression compared to CD8 High T cells which expressed elevated KLRD1 (CD94) and granzyme B levels within the tumour microenvironment (TME). Spatial analysis revealed the presence of CD8 High T cells in close proximity to tumour cells, while the CD8 Low T cells resided at the tumour boundaries. Importantly, the number of tumour‐infiltrating CD8 Low T lymphocytes correlated with a poor prognosis as well as with enhanced cancer progression in human mammary carcinoma. We also found a reduced frequency of CD8 Low T lymphocytes in a cohort of relapse (disease active) multiple sclerosis patients compared to healthy subjects during immune cell starvation in vitro. Conclusions: In summary, our data show that functionally distinct cytotoxic T lymphocytes can be identified based on their expression of CD8. Indicating a more general role in CD8 T cell immunity, these cells may play opposing roles in the TME, and also in the pathophysiology of autoimmune diseases such as multiple sclerosis. Abstract : Transcriptome analysis and functional characterisation reveals distinct phenotypes of human CD8 Low ‐ and high‐expressing cytotoxic T cells. CD8 Low T cells versus CD8 High T cells show divergent localisation patterns in tumours and are associated with patient prognosis. Reduction in CD8 Low compared to CD8 High T cells in RRMS patients experiencing relapse.